DESIGN THINKING IN MATHEMATICS EDUCATION FOR PRIMARY SCHOOL: A SYSTEMATIC LITERATURE REVIEW - Muhammad Zaim George Man; Riyan Hidayat; Mohamad Khairuzzamir Kashmir; Nurul Fatihah Suhaimi; Mashitah Adnan; Azizah Saswandila (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
Design Thinking is a knowledge as a thriving innovation practice and an approach to creative problem solving. The main purpose of this study is to review existing studies which are related to the Design Thinking in Mathematics Education for primary school. The search terms were used by inserting the suitable keywords based on the main topic such as